Vesicle adhesion in the electrostatic strong-coupling regime studied by time-resolved small-angle X-ray scattering. Issue 17 (22nd April 2020) - Komorowski, Karlo; Schaeper, Jannis; Sztucki, Michael; Sharpnack, Lewis; Brehm, Gerrit; Köster, Sarah; Salditt, Tim
Abstract : We have used time-resolved small-angle X-ray scattering (SAXS) to study the adhesion of lipid vesicles in the electrostatic strong-coupling regime induced by divalent ions. Abstract : We have used time-resolved small-angle X-ray scattering (SAXS) to study the adhesion of lipid vesicles in the electrostatic strong-coupling regime induced by divalent ions. The bilayer structure and the interbilayer distance d w between adhered vesicles was studied for different DOPC:DOPS mixtures varying the surface charge density of the membrane, as well as for different divalent ions, such as Ca 2+, Sr 2+, and Zn 2+ . The results are in good agreement with the strong coupling theory predicting the adhesion state and the corresponding like-charge attraction based on ion-correlations. Using SAXS combined with the stopped-flow rapid mixing technique, we find that in highly charged bilayers the adhesion state is only of transient nature, and that the adhering vesicles subsequently transform to a phase of multilamellar vesicles, again with an inter-bilayer distance according to the theory of strong binding. Aside from the stopped-flow SAXS instrumentations used primarily for these results, we also evaluate microfluidic sample environments for vesicle SAXS in view of future extension of this work.